bài 1:Tìm y
\(y:\dfrac{3}{5}-\dfrac{1}{5}=\dfrac{1}{2}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`3/11 xx 1 5/7 xx 2 4/9 xx 1 5/8 xx 21/26`
`=3/11 xx 12/7 xx 22/9 xx 13/8 xx 21/26`
`=(3 xx 12 xx 22 xx13 xx 21)/(11 xx 7 xx 9 xx 8 xx 26)`
`=(3 xx 3 xx 4 xx 11 xx 2 xx 13 xx 7 xx 3)/(11 xx 7 xx 3 xx3 xx 2 xx 4 xx 13 xx 2)`
`= 3/2`
3/11 x 1 5/7x 2 4/9 x 1 5/8 x 21/26
= 3/11 x 12/7 x 22/9 x 13/8 x 21/26
= 3x12x22x13x21/ 11x7x9x8x26
= 3x3x4x2x11x13x7x3 / 11x7x3x3x4x2x13x2
= 3/2 ( sử dụng cách triệt tiêu)
`y : 3/5 - 1/5 = 1/2`
`y : 3/5 = 1/2 + 1/5`
`y : 3/5 = 5/10 + 2/10`
`y :3/5 = 7/10`
`y=7/10 xx 3/5`
`y= 21/50`
Vậy `y= 21/50`
`y:3/5-1/5=1/2`
`y:3/5=1/2+1/5`
`y:3/5=7/10`
`y=7/10`x`3/5`
`y=21/50`